Advancing the understanding of placebo effects in psychological outcomes of exercise: Lessons learned and future directions - Lindheimer, J. B.; Szabo, A.; Raglin, J. S.; Beedie, C. (European Journal of Sport Science, 2020)
Despite the apparent strength of scientific evidence suggesting that psychological benefits result from both acute and chronic exercise, concerns remain regarding the extent to which these benefits are explained by placebo effects. Addressing these concerns is methodologically and at times conceptually challenging. However, developments in the conceptualisation and study of placebo effects from the fields of psychology, neuroscience, pharmacology, and human performance offer guidance for advancing the understanding of placebo effects in psychological responses to exercise. In clinical trials, expectations can be measured and experimentally manipulated to better understand the influence of placebo effects on treatment responses. Further, compelling evidence has shown that the contribution of placebo effects and their underlying neurobiological mechanisms to treatment effects can be measured without administering a traditional placebo (e.g. inert substance) by leveraging psychological factors such as expectations and conditioning. Hence, the purpose of this focused review is to integrate lessons such as these with the current body of literature on placebo effects in psychological responses to exercise and provide recommendations for future research directions.